1076. What Is the Positivity Delay of Blood Cultures in Infective Endocarditis?. (26th November 2018) - Issa, Nahema; Peuchant, Olivia; Lecomte, Raphael; Machelart, Irene; Greib, Carine; Wirth, Gaetane; Camou, Fabrice
Abstract: Background: Blood culture is a key test for the positive diagnosis of infective endocarditis (IE). In order to detect certain so-called fastidious bacteria and to avoid the absence of documentation, it is customary to repeat the blood cultures (at least three series) and to keep them for 21 days. However, objective data regarding the positivity delay of blood cultures in case of infective endocarditis are lacking. Methods: To determine the time to positivity of blood cultures during IE, all patients with documented IE by bacterial blood culture and presented to the Endocarditis team of our center were prospectively included. The study was conducted in a university hospital between 2013 and 2017. Results: During the study, 441 patients with IE were hospitalized and 401 IE had a bacteriological documentation (91%), including 380 by blood cultures. In 21 cases, the bacteriological documentation was made by serological tests or specific PCR assays. Information on positivity delay was available for 237 patients (135 IE on native valve and 102 on prosthetic valve) and 183 of them (77%) had 4 aero-anaerobic series or more blood cultures. Of the 988 series sampled, 978 (99%) were positive. The main documented bacteria were staphylococci (41%), streptococci (32%), and enterococci (21%). The median time to positivity of the first blood culture was 11.4 hours [interquartile = 7.3 hours–16.7 hours] and the maximum delay was 93 hours. There was no difference in positivity delay between the 123 community acquired IE and the 114 healthcare-associated IE: 11.2 hours vs. 11.4 hours. The median growth time was 9.9 hours for S. aureus vs. 18 hours for coagulase negative staphylococci, 11 hours for enterococci and 10.4 hours for streptococci. In the case of IE complicated by extracardiac emboli, the median positivity delay was 9.7 hours in the case of S. aureus vs. 12.3 hours for the other bacteria. Conclusion: In case of IE, our study shows that the median time positivity of the first blood culture is about 11 hours and no blood culture becomes positive beyond the fourth day. Slow-growing bacteria are identified by other diagnostic methods. We can, therefore, wonder about the need to multiply and conserve blood cultures beyond a week to document IE. Disclosures: All authors: No reported disclosures.